Patient–Physician Alignment in Satisfaction With Psoriatic Arthritis Treatment: Analysis From a Cross-Sectional Survey in the United States and Europe. Issue 4 (October 2020) - Gossec, Laure; Orbai, Ana-Maria; Lobosco, Steve; Moon, Rachel; Massey, Olivia; Piercy, James; Cappelleri, Joseph C.; Fallon, Lara; Young, Pamela; Romero, Ana-Belen; Hsu, Ming-Ann
Background: There is evidence that patients and physicians are frequently misaligned in their perspectives on psoriatic arthritis (PsA) treatment priorities, which may be associated with increased disease activity, greater disability, and poorer health-related quality of life of PsA patients. Objective: To identify factors associated with patient–physician misalignment in satisfaction with PsA disease control. Methods: In a cross-sectional survey of physicians and their patients with PsA from the United States and Europe, satisfaction with disease control was examined and classified as satisfied, neutral, or dissatisfied. Bivariate and multivariate regression analyses explored alignment in satisfaction between physicians and patients. Results: There were 656 PsA patient–physician pairs included in the analysis. Misalignment occurred in 20.6% of cases. Greater disease impact, worse physician-reported disease severity, and lower patient-reported involvement in treatment decisions were associated with misalignment. Conclusion: Greater patient–physician engagement may improve satisfaction, alignment, and outcomes in PsA disease control.